Understanding European Union Climate Change Governance through Political Parties Euromanifesto - Nur, Asrul Ibrahim (Faculty of Law, Mulawarman University, 2023)
This study offers a novelty specifying climate change as the legislation results in the European Parliament (EP) as an indicator of the consistency of political groups in realising their Euromanifestos. The article aims to investigate precisely the prospects and future of climate change policies in the EU post the 2019 general election. This study adopted qualitative legal research methods by studying the Euromanifestos of political groups in the European Union that competed in the 2019 European elections. Environmental issues, particularly climate change, were a significant focus in the study of these manifestos. Based on data from Euromanifesto, this study selected five EU Regulations as indicators of realising such political promises. In addition, the record of legislation and the results of voting during the establishment of the regulation was also applied as a data source in this study. In general, the cohesion between political groups in the EP is excellent. Based on a manifesto study, there are three essential findings; namely, most political groups in the EP make environmental issues, especially climate change, a politicised issue in elections. The second finding is that there are specific intersections between political groups, so it has implications for making the issue of climate change a common interest, and the results of the vote showed that a majority of Member of European Parliament members supported the establishment of the regulation. Finally, the solidarity of the EP political group cohesion in establishing regulations related to climate change is the last finding in this research.